mHealth Interventions for Preventing and Managing Childhood Obesity: An Integrative Review of Efficacy, Parental Involvement, and Physical Activity Outcomes - Dhiman, Ranjana; Rai, Kanika (National Journal of Community Medicine, 2025)
Introduction: Childhood obesity is a rapidly expanding issue that has long-term repercussions. Innovative mHealth interventions, such as web-based programs and mobile applications, have been implemented to assist in the prevention and management of pediatric obesity. The present review primarily concentrates on the most recent evidence regarding the efficacy of mHealth innovations that contribute to reducing childhood obesity through the promotion of physical activity and parental support. Methodology: A comprehensive analysis of 12 randomized controlled trials, 1 quasi-experimental research design, 1 mixed-method study, 6 meta-analysis, integrative review and systematic review (total n=20) was done to evaluate the effect of mHealth interventions on obesity among children. Results: The review's results indicated that mHealth interventions are beneficial for the significant reductions in BMI z-scores, as well as for the enhancement of their physical activity and dietary habits e.g. BMI z-score SMD -0.35 to -0.21; p<0.05; PA outcomes SMD ≈0.30-0.40. The behaviour of the children is influenced by the involvement of the parents through the web or the use of innovations, which in turn facilitates lifestyle modifications. The likelihood of success is increased for programs that incorporate a variety of components, such as education, monitoring, and personalized feedback. But altogether, the whole evidence is limited by short follow-up durations and predominance of high-income country studies. Conclusion: mHealth interventions, when multi-component and parent-involved, are effective and scalable for integration into primary care.